Research data management and its role in developing scientific research - Mousa, Tahani Mohammed (Journal of Humanities & Social Sciences, 2023)
The study aimed to identify the management of research data, its types, the life cycle of data, provide models for it, how to plan for managing it, and provide a number of tools to assist in the process of creating a plan for managing this data, documenting and sharing it, and the most important guidelines for its management. The study also reviews the role that research data management can contribute to the development of scientific research. The study used the descriptive analytical approach to analyze and explain the subject of the study. The study revealed the concept of managing research data, and what the data goes through from different stages, called the data life cycle, with mentioning models for it, and explained that writing and formulating a plan for it has become an essential part of academic research. There are a number of tools that help in the development of plans issued by various bodies and institutions. The study also revealed the importance of managing research data in contemporary times, where sharing and reusing data to reproduce and build on research is the cornerstone of open science. It also helps sustain the research, and use of its data in the long term .The researcher recommended research institutions and researchers to develop policies to manage their research data, and work to benefit from the models and tools that help in setting and developing the plan in a way that benefits the development of scientific research, strive to follow international standards, and work on conducting more studies and research to enrich knowledge of research data, its management and its importance.
Keywords: research data management; data life cycle; research data management plan